REMARKS ON THE FORMULA FOR THE MOMENTS OF THE PÓLYA PROBABILITY DISTRIBUTION - Gerstenkorn, Tadeusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
ABSTRACT The probability distribution of a random variable can be characterized by some numbers called parameters of the distribution. The moments belong to the most frequently used parameters. We focus on the Pólya distribution because it is easy to obtain from it as special cases some very important in the statistics distributions, as binomial, negative binomial and Poisson (the last one in the limit procedure). In 1972 G. Mühlbach gave very interesting formulae for the moments of the Pólya distribution. The author did not investigate the evaluation of the numerical efficacy of the formula for the moments. We will show that it is possible to demonstrate this formula in a simpler form, which has a practical significance and importance.